The off feeding intervals effect on some performance traits of broilers: S. Kh. Ahmed and G.Y. Butris - Ahmed, S. Kh. (The Iraqi Journal of Veterinary Medicine, 2014)
This study was conducted to evaluate the effect of feed restricted (off-feeding intervals) on feed intake, water intake, body weight gain, growth rate, feed conversion ratio, mortality, and dressing percentage of broilers. Two hundred fourty, one day old unsexed, (Ross 308) broiler chicks were randomly distributed into four treatment groups. Each group included three replicates each one had 20 birds. Those assigned as; Control group (T1): birds were fed ad libtium, T2 group feed removed from 8 Am. to 4 Pm., T3 group feed removed from 4 Pm. to 8 Am., T4 group feed removed 8 Am. to 8Am. (skip-a day) all birds were allowed to access feed for above intervals for 8-21 days of age, and re-full fed for the remaining of experiment period 42 days. The results indicated that feed restriction system did significantly (P<0.05) affect live body weight, body weight gain, and feed conversion ratio on starter diet period. Feed restriction significantly P<0.05 reduced feed consumption accompanied with water consumption positively correlated, decreases mortality in restriction period and at marketing, and increase dressing percentage, improved characteristics of carcasses at marketing age, the compensatory growth may be appeared after re-full free feeding for restricted groups to reach a close the market weight as control group., that was indicated by an increase in growth rate post feed restriction period especially at week (6th) as compared with the control group